Rivoluzioni civili, rivoluzioni musicali: il caso Monk - Fronzi, Giacomo (Scenari, 2021)
The relationship between “freedom” and “art” may seem obvious, first of all because it is constitutive of the creative and productive moment of art. From a social point of view, the artist enjoys a high degree of freedom and almost complete independence in the context of his profession. However, in some cases, the exercise and practice of freedom in art mean (or have meaning) much more than simply art freedom, going beyond itself. Often, freedom in art becomes the way to affirm denied rights, to achieve a higher degree of “humanity”. However, it is a matter of identifying a representative model of what has just been said, a figure capable of restoring this idea of art freedom that overcomes the confines of itself and interacts with the surrounding world, trying to influence its development. In these pages I will try to verify the thesis that the freedom of art has much to do with human freedom and demonstrate how this model can be embodied by Thelonious Monk.